Generation of a low temperature NO linkage isomer in a transition metal complex of group 9: K[IrCl5NO] - Guida, Jorge Alberto (2013)
The [IrCl5NO]−1 ion in the potassium salt can be partially transformed into a metastable state by light irradiation in the violet-near UV region at low temperature (77 K). The excitation process was followed by infrared spectroscopy, comparing the spectra before and after irradiation. A new band grew at 1812 cm−1 after irradiation with light in the 308–420 nm spectral region. The metastable state behavior is verified as this band decays upon heating the samples above 90 K or by subsequent irradiation using 450–680 nm light. The band at 1812 cm−1 was assigned to ν(NO) of metastable state 1 (or an IrON linkage isomer) for comparison with the band position reported for other transition metal nitrosyls. To our knowledge, this is the first generation of a M-ON linkage isomer reported for a nitrosyl of transition metal of group 9. Its behavior is similar to that observed in other nitrosyl complexes of group 8.